The Czechoslovak Crisis of 1948 in the Perception of American Diplomats and Media - A. V. Zorin (Vestnik MGIMO-Universiteta)
In February 1948, during the political crisis in Czechoslovakia was established a communist regime. This event completed the formation of the Soviet bloc in Europe. It directly impacted the US containment policy towards the USSR and the escalation of the Cold War. Based on archival documents and newspapers articles, the research studies these events through their perception by American media and diplomats, whose opinions and interpretations had great and decisive importance for the US public opinion and its government official reaction. The author concludes that the Czechoslovak crisis of 1948 aroused considerable interest and severe reaction in the United States. It was considered as a part of growing Soviet-American contradictions and international tension. Despite the fears of a communist coup in Czechoslovakia expressed back in 1947, American experts could not accurately predict the onset time of the crisis and its nature. The rapidity of the crisis, the Communist’s reaction, and decisiveness, lack of direct Soviet intervention, as well as the absence of democratic resistance, became a surprise for American journalists and diplomats. They believed that the communist takeover was a manifestation of Soviet expansion and the Kremlin’s desire to consolidate its control over all Eastern Europe. Despite the external legitimacy, the transfer of power to the left forces was interpreted as a coup d'état that final ized the establishment of the totalitarian regime in Czechoslovakia. Nevertheless, the US government refused to sever diplomatic relations with Prague and to initiate an international investigation. Washington found no direct evidence of Soviet intervention. It had to accept the changes in Czechoslovakia, focusing its forces on the inadmissibility of this scenario in Western Europe. The crisis directly influenced the adoption of the Marshall Plan and the intensification of the containment policy.